Genome-Wide RNAi Screen Identify Melanoma-Associated Antigen Mageb3 Involved in X Chromosome Inactivation. Issue 17 (17th August 2018) - Li, Wei; Hong, Ru; Lai, Lan-Tian; Dong, Qiman; Ni, Peiling; Chelliah, Rosi; Huq, Mehnaz; Ismail, Siti Nadirah Binte; Chandola, Udita; Ang, Zhiwei; Lin, Bingqing; Chen, Xin; et al.
Abstract: Xist ( i nactivated X chromosome s pecific t ranscript) is a prototype long noncoding RNA in charge of epigenetic silencing of one X chromosome in each female cell in mammals. In a genetic screen, we identify Mageb3 and its homologs Mageb1 and Mageb2 as genes functionally required for Xist -mediated gene silencing. Mageb1–3 are previously uncharacterized genes belonging to the MAGE (melanoma-associated antigen) gene family. Mageb1–3 are expressed in undifferentiated ES cells and early stages of in vitro differentiation, a critical time window of X chromosome inactivation. Mageb3 showed both cytoplasmic and nuclear localization without enrichment on the inactive X (Xi). Mageb3 interacted with Polycomb group ring finger 3 (Pcgf3), a RING finger protein involved in recruiting Polycomb activities onto Xi. Mageb3 overexpression stabilized Pcgf3 protein. Mageb1–3 gene knockout affected H3K27me3 enrichment and the spreading of gene silencing along Xi. These data suggested that Mageb3 might regulate the recruitment of the Polycomb complex onto Xi and subsequent H3K27me3 modification through Pcgf3. Moreover, the nucleolar enrichment of Mageb3 was diminished when nuclear matrix factor hnRNP U is overexpressed, implying the interaction between Mageb3 and nuclear matrix, which is another possible mechanism for Mageb3 to regulate X chromosome inactivation. Graphical abstract: Unlabelled Image Highlights: Mageb3 affects the gene-silencing pattern in X chromosome inactivation. Mageb3 binds and stabilizes Pcgf3. The subcellular localization of Mageb3 is influenced by hnRNP U.